Quantification of patient-specific coronary material properties and their correlations with plaque morphological characteristics: An in vivo IVUS study. (15th January 2023) - Wang, Liang; Maehara, Akiko; Zhang, Xiaoguo; Lv, Rui; Qu, Yangyang; Guo, Xiaoya; Zhu, Jian; Wu, Zheyang; Billiar, Kristen L.; Zheng, Jie; Chen, Lijuan; Ma, Genshan; et al.
Abstract: Background: A method using in vivo Cine IVUS and VH-IVUS data has been proposed to quantify material properties of coronary plaques. However, correlations between plaque morphological characteristics and mechanical properties have not been studied in vivo. Method: In vivo Cine IVUS and VH-IVUS data were acquired at 32 plaque cross-sections from 19 patients. Six morphological factors were extracted for each plaque. These samples were categorized into healthy vessel, fibrous plaque, lipid-rich plaque and calcified plaque for comparisons. Three-dimensional thin-slice models were constructed using VH-IVUS data to quantify in vivo plaque material properties following a finite element updating approach by matching Cine IVUS data. Effective Young's moduli were calculated to represent plaque stiffness for easy comparison. Spearman's rank correlation analysis was performed to identify correlations between plaque stiffness and morphological factor. Kruskal-Wallis test with Bonferroni correction was used to determine whether significant differences in plaque stiffness exist among four plaque groups. Result: Our results show that lumen circumference change has a significantly negative correlation with plaque stiffness ( r = −0.7807, p = 0.0001). Plaque burden and calcification percent also had significant positive correlations with plaque stiffness ( r = 0.5105, p < 0.0272 and r = 0.5312, p < 0.0193) respectively. Among the four categorized groups, calcified plaques had highest stiffness while healthy segments had the lowest. Conclusion: There is a close link between plaque morphological characteristics and mechanical properties in vivo. Plaque stiffness tends to be higher as coronary atherosclerosis advances, indicating the potential to assess plaque mechanical properties in vivo based on plaque compositions. Highlights: Strong correlations between coronary plaque morphological characteristics and mechanical properties were found in vivo. Several morphological factors had the potential to assess in vivo plaque stiffness due to their significant correlations. Plaque components had a great influence on the plaque stiffness. Among four plaque groups, calcified plaque had highest stiffness while healthy vessel had the lowest. And fibrous and lipid-rich plaques had intermediate plaque stiffness.